DISIPLIN KERJA DALAM MEMEDIASI PEMBERIAN REWARD DAN PUNISHMENT PADA KINERJA KARYAWAN BANK X CABANG SURABAYA - Annora Putri Eka Wati; Erika Suci Armadani; Yanuar Fauzuddin (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study aims to determine how the effect of reward and punishment on employee performance through work discipline at the Bank X Branch of Surabaya. This research uses quantitative research with an explanatory approach. The variables used are independent variables consisting of reward and punishment, thedependent variable is employee performance, the variable Interving work discipline. The population in this study were all employees of the Bank X branch of Surabaya, which amounted to 117 people. Collecting primary data using questionnaires and interviews. The data analysis technique used in this study is descriptive data analysis, regression analysis, hypothesis testing, and path analysis with the help of the SPSS 25 program. The results of this study indicate that Reward has a significant effect on employee discipline at Bank X Surabaya Branch. Punishment has a significant effect on the work discipline of employees of Bank X Surabaya Branch. Work discipline has a significant effect on employee performance at Bank X Surabaya Branch. Reward has a significant effect on employee performance at Bank X Surabaya Branch. Punishment has a significant effect on employee performance at Bank X Surabaya Branch. Reward has an effect on the performance of the employees of Bank X Surabaya Branch. Punishment affects the performance of the employees of Bank X Surabaya Branch.